Can Blood Oxygenation Level Dependent Functional Magnetic Resonance Imaging Be Used Accurately to Compare Older and Younger Populations? A Mini Literature Review - Wright, Melissa E.; Wise, Richard G. (Frontiers in Aging Neuroscience, 2018)
A wealth of research has investigated the ageing brain using blood oxygenation level dependent functional MRI (BOLD fMRI). However, many studies do not consider the ageing of the cerebrovascular system, which can influence the BOLD signal independently from neural activity, limiting what can be inferred when comparing age groups. Here, we discuss the ways in which the ageing neurovascular system can impact BOLD fMRI, the consequence for age-group comparisons and possible solutions. While BOLD fMRI is a valuable tool in this context, it is hoped that this review will highlight the importance of correction and consideration of vascular confounds.